Preparation method of Cu-Pd alloy modified bismuth titanate nanorod
Through the Cu-Pd alloy, the problem of insufficient active sites and complex reactions of single metal catalysts in carbon dioxide reduction reaction is solved, and high-efficiency photocatalytic reduction of carbon dioxide is achieved, with high yield and excellent selectivity.
Patent Information
- Application Number
- CN202411269562.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-11
- Publication Date
- 2025-02-14
AI Technical Summary
The existing single metal catalysts have problems such as insufficient active sites, complex reaction steps and difficulty in separation of intermediates in carbon dioxide reduction reaction, which leads to difficulty in reducing carbon dioxide light to polycarbon products.
The method of modifying Bi4Ti3O2 nanorods was used to modify the Bi4Ti3O2 nanorods by Cu-Pd alloy, and the Cu-Pd alloy was prepared by hydrothermal method and chemical precipitation steps, and the catalytic activity and selectivity were improved using bimetallic sites.
High-efficiency photocatalytic reduction of carbon dioxide is achieved, with high yield and excellent selectivity, and can generate multi-carbon products such as ethanol, which significantly improves the photocatalytic performance of the catalyst.
Smart Images

Figure CN119425722A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for preparing Cu-Pd alloy modified bismuth titanate nanorods. The Cu-Pd alloy modified bismuth titanate nanorods prepared in this way can be used in the field of photocatalysis, such as photocatalytic reduction of carbon dioxide, and belongs to the field of new material technology. Background Art
[0002] In recent years, most metal elements have attracted extensive attention due to their advantages of large electron storage capacity and high electron transfer rate, and their applications in lithium-ion batteries, gas sensors, photocatalysis, dye-sensitized solar cells, etc. In particular, in the field of photocatalytic reduction of CO2, the metal modification strategy is usually to anchor metal nanoparticles on a solid matrix and composite them with photocatalytic semiconductor materials to form a co-catalyst, which absorbs solar energy as a light collection center, so that solar energy can be coupled to the catalytic reaction. This energy coupling can not only accelerate the chemical reaction on the surface of the photocatalyst, but also provide a driving force for non-spontaneous reactions in the dark. Or as an active site, it interacts with reactants (or reaction intermediates), participates in the reduction of CO2, accelerates the separation of electron-hole pairs, and enhances the transport through the interface formed between the semiconductor substrate and the co-catalyst, thereby improving the photocatalytic performance of semiconductor photocatalysts, improving the stability of products, and even changing the reaction pathway. However, in the reaction process of carbon dioxide reduction of C2 or multi-carbon products, the carbon-carbon (CC) coupling process can only occur between adjacent active sites. Isolated single metal sites cannot meet the synergistic effect of multiple sites. In addition, the carbon dioxide reduction process involves extremely complex multi-step reactions, which require the participation of multiple intermediates. Isolated single metal sites cannot meet the requirements for the adsorption of multiple intermediates, which greatly limits the application of single metal catalysts in CO2 reduction reactions and makes the photoreduction of CO2 to multi-carbon products difficult. Compared with isolated single metal sites, bimetallic alloys not only have the advantages of single metals, but also show more other advantages: (1) alloy sites can increase the metal loading and the number of active sites; (2) bimetallic sites show more flexible active site structural fusion, providing the synergistic multi-sites required for complex CO2 reduction reactions; (3) the intermediate adsorption characteristics of active sites can be adjusted between different single metal sites, providing more possibilities for the optimization of reaction processes and product selectivity; (4) in bimetallic catalysts, one metal site can activate the support and then change the interaction between the support and the other metal, thereby initiating the catalytic reaction. (5) independent coexisting bimetallic sites can obtain various products at different reaction sites. In terms of the value and energy density of CO2 reduction products, C2 or multi-carbon products play a more significant role. Therefore, designing and optimizing active sites to improve the selectivity and activity of target products are the key points of CO2 reduction research. It is very necessary to develop a simple, efficient, energy-saving method for preparing bimetallic modified bismuth titanate nanomaterials with high activity and high selectivity.
[0003] CN201510946933.4 discloses a gadolinium-doped bismuth titanate visible light photocatalyst, wherein the molar ratio of bismuth atoms to gadolinium atoms in the gadolinium-doped bismuth titanate is 39:1 to 9:1; and the surface of the gadolinium-doped bismuth titanate is loaded with metal platinum particles. The present invention also discloses a method for preparing a gadolinium-doped bismuth titanate visible light photocatalyst, wherein bismuth nitrate, gadolinium nitrate and tetrabutyl titanate are used as raw materials, glacial acetic acid, ethylene glycol methyl ether and acetylacetone are used as solvents, a gadolinium-doped bismuth titanate carrier is synthesized by a sol-gel-hydrothermal method, and then chloroplatinic acid is adsorbed on the surface of the gadolinium-doped bismuth titanate by an aqueous solution of chloroplatinic acid impregnation method, and finally platinum particles are loaded on the surface of the gadolinium-doped bismuth titanate by high temperature calcination. Summary of the invention
[0004] The purpose of the present invention is to provide a method for preparing Cu-Pd alloy modified Bi4Ti3O2 nanorods, which prepares Cu-Pd alloy modified Bi4Ti3O2 nanorods under original simple operation steps.
[0005] The present invention also aims to provide a use of Cu-Pd alloy modified Bi4Ti3O2 nanorods, that is, Cu-Pd alloy modified Bi4Ti3O2 nanorods are used for photocatalytic reduction of carbon dioxide.
[0006] The technical scheme of the present invention is: a preparation method of Cu-Pd alloy modified Bi4Ti3O2 nanorods, comprising the following steps: (1) uniformly dissolving bismuth nitrate pentahydrate, tetrabutyl titanate and hexadecyltrimethylammonium bromide in a sodium hydroxide solution to obtain a milky white suspension; then placing the mixture in an anti-corrosion lining autoclave at 180±20°C for reaction for 24±10h, and collecting the product after washing and drying; (2) dispersing the above product in deionized water, adding a certain amount of copper nitrate trihydrate and palladium nitrate dihydrate after ultrasonic treatment, and then dropwise adding 0.08-0.12 mol L -1 Sodium borohydride was added and stirred to ensure that the reagent was completely dissolved; finally, the obtained sample was washed several times and the obtained Cu x Pd y -BTO sample; or centrifuged and washed and freeze-dried to obtain Cu x Pd y -BTO samples;
[0007] The molar ratio of bismuth nitrate pentahydrate, tetrabutyl titanate and hexadecyltrimethylammonium bromide is 4:3:3.5; the total mass of bismuth nitrate pentahydrate and tetrabutyl titanate is 10-20% of the mass of the sodium hydroxide solution;
[0008] After ultrasonic treatment, a certain amount of copper nitrate trihydrate (x) and palladium nitrate dihydrate (y) were added to the bismuth nitrate pentahydrate, tetrabutyl titanate and hexadecyltrimethylammonium bromide, and then 1 mL of sodium borohydride (0.1 mol L-1 ), magnetic stirring for 1 h;
[0009] The molar ratio of copper nitrate trihydrate to palladium nitrate dihydrate is 1:0, 0:1, 1:1, 1:4, 1:6;
[0010] Sodium hydroxide solution is 2-4 mol L -1 Sodium hydroxide solution.
[0011] For example, when the molar ratio of Cu:Pd is 4:1, 10 mmol L -1 Copper nitrate trihydrate and palladium nitrate dihydrate solutions,
[0012] Bismuth nitrate pentahydrate, tetrabutyl titanate and hexadecyltrimethylammonium bromide were uniformly dissolved in a sodium hydroxide solution, and then the mixture was placed in a 100 mL Teflon-lined autoclave at 180° C. for 24 h.
[0013] First, proper amounts of bismuth nitrate pentahydrate, tetrabutyl titanate and hexadecyltrimethylammonium bromide are mixed and dissolved in a sodium hydroxide solution, and stirred continuously for more than 1 hour to achieve uniform dispersion.
[0014] The above product was washed and dried, and 0.1 g was weighed and dissolved in 50 mL of water and ultrasonicated for 1 h to ensure complete dispersion. Different proportions of copper nitrate trihydrate and palladium nitrate dihydrate were added dropwise to the above solution and stirred for 1 h to ensure complete adsorption, wherein 10 mmol L copper nitrate trihydrate solution and palladium nitrate dihydrate solution were pre-prepared. -1 In case of need for dropwise addition.
[0015] Pre-prepared 0.1 mol L -1 Sodium borohydride solution, and then sodium borohydride is added dropwise to the above mixed solution with stirring, the volume ratio of sodium borohydride to the aqueous solution containing bismuth titanate is 1:50.
[0016] After stirring, the product is first washed with deionized water by centrifugation until it becomes neutral, and then washed several times with anhydrous ethanol and deionized water, followed by freeze drying for as long as 4-7 days to obtain Cu-Pd alloy modified Bi4Ti3O2 nanorods.
[0017] The Cu-Pd alloy modified Bi4Ti3O2 nanorods obtained by the preparation method are used for photocatalytic reduction of carbon dioxide.
[0018] The freeze drying time is 4-7 days, or vacuum drying is adopted, the drying temperature is 60°C, and the time is 8-16 hours. Thus, Bi4Ti3O2 nanorods modified by Cu-Pd alloy are obtained, and the use of them in photocatalysis can achieve good results.
[0019] The method includes using three precursor materials - bismuth nitrate pentahydrate, tetrabutyl titanate and hexadecyl trimethyl ammonium bromide, adding them to a sodium hydroxide solution at a molar ratio of 4:3:3.5, stirring and mixing evenly, and then obtaining a precursor through a one-step hydrothermal step, centrifugally washing and drying it, and then adding different proportions of metal nitrates - copper nitrate trihydrate and palladium nitrate dihydrate for adsorption, and finally adding sodium borohydride to reduce it to obtain Cu-Pd alloy-modified Bi4Ti3O2 nanorods. This method only requires simple hydrothermal and chemical precipitation steps, while the general "bottom-up" or "top-down" strategy often requires multiple operation steps.
[0020] The key to the method of the present invention is to simultaneously dissolve two metal salt materials in the precursor for reduction reaction. This method using only one step of chemical precipitation may be applied to synthesize single / multi-metal modified bismuth titanate nanomaterials with more appropriate amounts of metal salts. The principle of the amount of metal salt used is: the molar ratio of metal ions is the volume ratio taken from a fixed concentration of metal salt solution.
[0021] Since the highly dispersed and fully exposed Cu-Pd alloy sites are conducive to CO2 adsorption and significantly reduce the generation energy barrier of the reaction intermediate *OCCO, more multi-carbon products can be generated. At the same time, the introduction of bimetallic sites improves the separation and transfer of photogenerated carriers in pure bismuth titanate, so Cu-Pd alloy-modified bismuth titanate nanorods are good photocatalytic materials. Using them for photocatalytic reduction of carbon dioxide can achieve good results.
[0022] The beneficial effects of the present invention are as follows: bismuth nitrate pentahydrate, tetrabutyl titanate and hexadecyltrimethylammonium bromide are mixed and dissolved in a sodium hydroxide solution and sealed for a high temperature and high pressure process, a precursor is obtained through a hydrothermal reaction step, and then two metal soluble salts, copper nitrate trihydrate and palladium nitrate dihydrate solution, are added to the aqueous solution at the same time, and an alloy modification is obtained through a chemical reduction step, and the steps are simple and convenient. Another raw material, copper nitrate trihydrate, is cheap, stable and non-toxic. At the same time, Cu-Pd modifies bismuth titanate to obtain a bimetallic site that interacts with the substrate material to produce a multi-carbon product ethanol, which not only has a high yield (56.74 μmol g under 5 hours of illumination). -1 ), and this structure is very beneficial for photocatalysis. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 : This is an X-ray diffraction (XRD) diagram of an embodiment of the present invention. The molar contents of Cu and Pd are 0:0, 1:0, 0:1, 1:1, 1:4, and 1:6, respectively. In the figure, it can be seen that all the diffraction peaks of the BTO nanorods are completely matched with the orthorhombic phase of BTO. x Pd y When the content is low, no diffraction peaks appear, and no impurity phases related to Cu and Pd are produced.
[0024] Figure 2 Unmodified Cu x Pd y SEM image of pure BTO alloy. It can be seen that BTO is a uniform rod-shaped nanostructure with a smooth surface and a length of up to hundreds of nanometers.
[0025] Figure 3 Transmission electron microscopy (TEM) images. Figure 3 (a) and 3(b) correspond to TEM images of the Cu4Pd-BTO product of the present invention at different magnifications. It can be seen that the product is a Cu4Pd alloy particle with a size of 5-10nm, which is evenly dispersed on the BTO nanorods. The high-resolution TEM image shows that the lattice fringes of 0.198nm are consistent with the (221) plane of Cu4Pd.
[0026] Figure 4 The EDS line mapping spectrum of the Cu4Pd alloy on the Cu4Pd-BTO product of the embodiment of the present invention indicates the formation of an ordered intermetallic structure of the nano-alloy.
[0027] Figure 5 This is the XPS graph of Cu4Pd-BTO. Figure 5 a is the full spectrum, which confirms the presence of Bi, Ti, O, Cu and Pd elements. Figure 5 b-5f are the XPS images of Bi 4f, Ti 2p, O1s, Cu 2p, and Pd 3d, respectively. The analysis results further show that Cu and Pd in the product are distributed in the form of alloy.
[0028] Figure 6 It is the KPFM diagram of the product BTO and Cu4Pd-BTO of the embodiment of the present invention. The analysis of the diagram confirms that the loaded Cu4Pd nano alloy can promote the charge separation of BTO nanorods. Figure 6 a and 6b show the surface morphologies of BTO and Cu4Pd-BTO on unirradiated silicon substrates. The surface photovoltage (SPV) images ( Figure 6 c and 6d). Cu4Pd-BTO shows a negative change of 45-50 mV along the white line, indicating that the concentration of photogenerated electrons has increased significantly, while BTO only has a negative change of 15-18 mV after illumination ( Figure 6 e and 6f). The results show that loading Cu4Pd nanoalloy can promote the charge separation of BTO nanorods.
[0029] Figure 7 The photocatalytic reduction of carbon dioxide by the product of the embodiment of the present invention produces CO( Figure 7 a), CH4( Figure 7 b), C2H6( Figure 7c) and C2H5OH( Figure 7 d) Activity, Cu x Pd y -BTO corresponds to the activity of products modified with different Cu and Pd contents. BTO is Cu-free x Pd y Activity of modified pure bismuth titanate products.
[0030] Figure 8 This is a comparison of the photocatalytic reduction of carbon dioxide products by the products of the embodiments of the present invention for one hour. DETAILED DESCRIPTION
[0031] Explanation of the attached table
[0032] Table 1 is a comparison of the selectivity data of the photocatalytic reduction of carbon dioxide products between Cu4Pd-BTO and BTO in the example products of the present invention. From the table, it can be seen that the electron selectivity and yield selectivity of BTO and Cu4Pd-BTO.
[0033] Table 1 is a comparison of catalyst selectivity
[0034] (1) Add 4 mmol of bismuth nitrate pentahydrate, 3 mmol of tetrabutyl titanate and 3.5 mmol of hexadecyltrimethylammonium bromide to 30 mL of deionized water. After vigorous stirring for 30 minutes, add 40 mL of 3 mol L -1 NaOH solution was dripped into the above precursor solution, and magnetic stirring was continued for 1 h to ensure that the reagent was completely dissolved. The mixed solution was then transferred to a 100 mL Teflon-lined autoclave, sealed, and heated at 180 °C for 24 h. The milky white powder was collected, washed, and dried at 60 °C to obtain Bi4Ti3O 12 (BTO) products;
[0035] (2) Disperse 0.1 g of the above-mentioned BTO powder into 50 mL of deionized water and ultrasonicate for 1 h. Then, a certain amount of copper nitrate trihydrate (10 mmol L -1 ) and palladium nitrate dihydrate (10 mmol L -1 ) was mixed into the suspension and stirred magnetically for 1 h;
[0036] (3) Add 1 mL NaBH4 (0.1 mol L) dropwise to the above mixture. -1 ), magnetic stirring to ensure complete dissolution of the reagents. Finally, the obtained samples were washed several times and dried at 70°C;
[0037] (4) The obtained sample is called Cu x Pd y-BTO, where x and y are the molar ratios of copper nitrate trihydrate and palladium nitrate dihydrate, respectively, so the catalysts are named Cu-BTO, Pd-BTO, CuPd-BTO, Cu4Pd-BTO, Cu6Pd-BTO. Good results can be achieved when used in photocatalysis.
[0038]
[0039] The products were analyzed using X-ray diffractometer (XRD), scanning electron microscope (SEM), transmission electron microscope (TEM), X-ray photoelectron spectrometer (XPS) and Kelvin probe force microscope (KPFM).
[0040] Figure 1 The XRD diagram of BTO products with different Cu and Pd contents in the embodiment of the present invention is shown in FIG. x Pd y No diffraction peaks appear, and no impurity phases related to Cu and Pd are produced. All diffraction peaks of BTO nanorods seen in the figure completely match the orthorhombic phase of BTO.
[0041] Figure 2 No modified Cu x Pd y From the SEM image of pure BTO alloy, we can see that BTO is a uniform rod-shaped nanostructure with a smooth surface and a length of up to hundreds of nanometers.
[0042] Figure 3 TEM image of BTO loaded with Cu4Pd alloy. Figure 3 (a) The size of Cu4Pd alloy particles is 5-10nm and is evenly dispersed on the BTO nanorods. Figure 3 (b) is a high-resolution TEM image showing that the lattice fringes of 0.198 nm are consistent with the (221) plane of Cu4Pd.
[0043] Figure 4 It is the EDS line mapping spectrum of Cu4Pd alloy on Cu4Pd-BTO, which shows that the distribution of Cu and Pd atoms is concentrated, and the distribution ratio is approximately 4:1, confirming the formation of ordered intermetallic structure of nano-alloy.
[0044] Figure 5 5a is the XPS graph of Cu4Pd-BTO, and 5b-5f are the XPS graphs of Bi 4f, Ti 2p, O1s, Cu 2p, and Pd 3d, respectively. Figure 5 In b, the two peaks at 159.1 eV and 164.5 eV are attributed to Bi 4f 7 / 2 and Bi4f5 / 2 , indicating that Bi is equal to Bi 3+ exists in the form of. Figure 5 Ti 2p in Cu4Pd-BTO in c 3 / 2 The peak exhibits a positive shift of 0.7 eV relative to the original BTO, indicating the electron transfer from BTO to the Cu4Pd alloy and confirming the strong electronic interaction between the Cu-Pd nanoalloy and the BTO substrate.
[0045] Application Examples
[0046] The Cu prepared in Example x Pd y The alloy-modified BTO nanorod photocatalyst was used to photocatalytically reduce CO2. Specifically, 0.02 g of the photocatalyst was weighed and evenly dispersed in a 4.2 cm 2 The volume of the whole reaction system is 170 mL, and the light source is a 300 W xenon lamp. Then, high-purity CO2 gas is introduced into the reaction system to make the pressure in the reaction system reach standard atmospheric pressure. Then, 0.4 mL of deionized water is injected into the system as a reducing agent. After dark adsorption for several hours, the light is turned on. At regular intervals, 5 mL of gas is taken out from the system and injected into a gas chromatograph to analyze the amount of CO, CH4, C2H6 and C2H5OH produced.
[0047] The relationship between the amount of CO, CH4, C2H6 and C2H5OH obtained and time is as follows Figure 7 and Figure 8 The results show that the loaded Cu x Pd y The alloyed BTO has better photocatalytic CO2 reduction activity than the original BTO. Only CO was observed on the original BTO nanorods, and only CO and CH4 were produced when Pd was loaded on BTO alone. After the Cu-Pd alloy was modified, CH4 and C2H5OH products and a small amount of CO and C2H6 were detected, indicating that CC coupling is more likely to occur on the Cu-Pd bimetallic site. The Cu4Pd-BTO with the best performance was selected to compare the selectivity with the original BTO. As shown in Table 1, the activity of the original BTO and the single metal Cu-BTO and Pd-BTO was effectively improved. At the same time, the electronic selectivity of Cu4Pd-BTO for ethanol reached 75.89%, and the yield selectivity reached 69.21%.
[0048] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations on the present invention. A person skilled in the art may change, modify, replace and modify the above embodiments within the scope of the present invention without departing from the principles and intent of the present invention.
Claims
1. A method for preparing Cu-Pd alloy modified Bi4Ti3O2 nanorods, characterized in that: The following steps are involved: (1) bismuth nitrate pentahydrate, tetrabutyl titanate and hexadecyltrimethylammonium bromide are uniformly dissolved in a sodium hydroxide solution to obtain a milky white suspension; the mixture is then placed in an anti-corrosion lining autoclave at 180±20°C for reaction for 24±10 hours, and the product is washed, dried and collected; (2) the above product is dispersed in deionized water, a certain amount of copper nitrate trihydrate and palladium nitrate dihydrate are added after ultrasonic treatment, and then 0.08-0.12 mol L -1 Sodium borohydride was added and stirred to ensure that the reagent was completely dissolved; finally, the obtained sample was washed several times and the obtained Cu x Pd y -BTO samples or freeze-dried to obtain Cu x Pd y -BTO samples; The molar ratio of bismuth nitrate pentahydrate, tetrabutyl titanate and hexadecyltrimethylammonium bromide is 4:3:3.5; the total mass of bismuth nitrate pentahydrate and tetrabutyl titanate is 10-20% of the mass of the sodium hydroxide solution; After ultrasonic treatment, a certain amount of copper nitrate trihydrate (x) and palladium nitrate dihydrate (y) were added to the bismuth nitrate pentahydrate, tetrabutyl titanate and hexadecyltrimethylammonium bromide, and then 1 mL of sodium borohydride (0.1 mol L -1 ), magnetic stirring for 1 h; The molar ratio of copper nitrate trihydrate to palladium nitrate dihydrate is 1:0, 0:1, 1:1, 1:4, 1:6; Sodium hydroxide solution is 2-4 mol L -1 Sodium hydroxide solution.
2. The method for preparing Cu-Pd alloy modified Bi4Ti3O2 nanorods according to claim 1, characterized in that: For example, when the molar ratio of Cu:Pd is 4:1, 10 mmol L -1 Copper nitrate trihydrate and palladium nitrate dihydrate solutions.
3. The method for preparing Cu-Pd alloy modified Bi4Ti3O2 nanorods according to claim 1, characterized in that: Bismuth nitrate pentahydrate, tetrabutyl titanate and hexadecyltrimethylammonium bromide were uniformly dissolved in a sodium hydroxide solution, and then the mixture was placed in a 100 mL Teflon-lined autoclave at 180° C. for reaction for 24 hours.
4. The method for preparing Cu-Pd alloy modified Bi4Ti3O2 nanorods according to claim 1, characterized in that: First, proper amounts of bismuth nitrate pentahydrate, tetrabutyl titanate and hexadecyltrimethylammonium bromide are mixed and dissolved in a sodium hydroxide solution, and stirred continuously for more than 1 hour to achieve uniform dispersion.
5. The method for preparing Cu-Pd alloy modified Bi4Ti3O2 nanorods according to any one of claims 1 to 4, characterized in that: The reaction time is 24 h at a temperature of about 180°C.
6. The method for preparing Cu-Pd alloy modified Bi4Ti3O2 nanorods according to any one of claims 1 to 4, characterized in that: The above product was washed and dried, and 0.1 g was weighed and dissolved in 50 mL of water and ultrasonicated for 1 h to ensure complete dispersion.
7. The method for preparing Cu-Pd alloy modified Bi4Ti3O2 nanorods according to any one of claims 1 to 4, characterized in that: Different proportions of copper nitrate trihydrate and palladium nitrate dihydrate were added dropwise to the above solution and stirred for 1 h to ensure complete adsorption. 10 mmol L copper nitrate trihydrate solution and 10 mmol L palladium nitrate dihydrate solution were prepared in advance. -1 In case of need for dropwise addition.
8. The method for preparing Cu-Pd alloy modified Bi4Ti3O2 nanorods according to any one of claims 1 to 4, characterized in that: Pre-prepared 0.1 mol L -1 Sodium borohydride solution, and then sodium borohydride is added dropwise to the above mixed solution and stirred for 1 hour, the volume ratio of sodium borohydride to the aqueous solution containing bismuth titanate is 1:
50.
9. The method for preparing Cu-Pd alloy modified Bi4Ti3O2 nanorods according to any one of claims 1 to 4, characterized in that: After stirring, the product was first washed with deionized water by centrifugation until neutral, and then washed several times with anhydrous ethanol and deionized water, followed by freeze drying for 4-7 days to obtain Cu-Pd alloy modified Bi4Ti3O2 nanorods.
10. The Cu-Pd alloy modified Bi4Ti3O2 nanorods obtained by the preparation method according to any one of claims 1 to 4, characterized in that: Used for photocatalytic reduction of carbon dioxide.
Citation Information
Patent Citations
Gadolinium-doped bismuth titanate visible light photocatalyst and preparation method thereof
CN105597751B